Central African Republic : Sixth Review Under the Arrangement Under the Extended Credit Facility and Financing Assurances Review-Staff Report; Debt Sustainability Analysis; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Central African Republic. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
Recent performance suggests further economic stabilization in the Central African Republic, but uncertainties remain related to the general elections. The fiscal program aims at supporting domestic demand, financing the peace process and the elections, and mobilizing more revenue. Structural reform measures are targeted to support the macrofiscal framework through revenue administration reform, better public financial management, and strengthened policy implementation capacity. Payment of government utility bills will help. Executive Directors encourage the authorities to secure bilateral agreements with all external creditors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet